Learning Goal Orientation, Innovative Work Behavior, and Entrepreneurship Training on Human Resources Development - Syaiful Arifin (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
Entrepreneurship training that has been provided continues to cause problems in developing human resources for Indonesian migrant workers. The unique character of Indonesian migrant workers who were initially employees who turned into business owners is interesting to research in relation to human resource development. Thus, this study aims to analyze the linkage between human resource development through the variables entrepreneurship training, innovative work behavior, and learning goal orientation. This study used questionnaire-based surveys with certain criteria and involved structural equation modeling (SEM) methods based on partial least squares (PLS). The data were collected from 354 Indonesian migrant workers who were involved in small-medium enterprises. The findings indicate that there is a positive relationship between entrepreneurship training and innovative work behavior. This study also shows that learning goal orientation moderates the influence of entrepreneurship training on innovative work behavior. Keywords: Entrepreneurship training, Innovative work behavior, Learning goal orientation, Human resources development